2019
DOI: 10.1097/md.0000000000017010
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis comparing intramedullary with extramedullary fixations for unstable femoral intertrochanteric fractures

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Few meta-analyses exist in literature comparing DHS alone to CMN for the management of these kinds of fractures [ 6 , 27 , 28 ]. However, most of the recent research demonstrated superior results of CMN to DHS alone when it comes to unstable trochanteric hip fractures management [ 6 , 8 , 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Few meta-analyses exist in literature comparing DHS alone to CMN for the management of these kinds of fractures [ 6 , 27 , 28 ]. However, most of the recent research demonstrated superior results of CMN to DHS alone when it comes to unstable trochanteric hip fractures management [ 6 , 8 , 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Failure in cases managed by DHS alone is believed to be due to excessive lag screw sliding with collapse or medialisation of the distal fracture fragment even if the lag screw is optimally positioned in the femoral head [ 6 , 27 , 28 ]. The theoretical reasons behind that are thought to be either loss of the calcar support or lateral femoral wall insufficiency resulting in fracture collapse with loading [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment for intertrochanteric fractures of the femur can be divided into conservative treatment and surgical treatment. Most doctors agree that conservative treatment of ITFs results in serious complications and sequelae, such as the need for bed rest and limb traction, and a mortality rate within 1 year after injury is relatively high. Surgical treatment achieves firm and stable internal fixation of the fracture and early functional training, and reduces complications due to long‐term bed rest.…”
Section: Introductionmentioning
confidence: 99%